TYPES OF CONCILIATION AGREEMENTS IN CIVIL PROCEEDINGS - Yesayan, Vard (State and Law, 2021)
In the framework of the presented work, the judicial-extrajudicial types of conciliation agreement in civil litigation, the ways of their expression, the procedure and peculiarities of the conclusion were studied and discussed. Within the framework of the work, the peculiarities of concluding a conciliation agreement in the enforcement proceedings were also referred to.